IMPLEMENTATION OF THE PROBLEM-BASED LEARNING (PBL)MODEL TO IMPROVE THE FIFTH-GRADE ELEMENTARY STUDENTS’INTEGRATED THEMATIC LEARNING OUTCOMES - Salsabila Nadya Putri; Mai Sri Lena (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper reports students’ learning outcomes by applying the Problem-Based Learning (PBL) model in class V at SDN 11 Kurao Pagang Padang in thematic learning. The research is CAR (Classroom Action Research) by applying qualitative and quantitative approaches. In order to obtain the expected learning outcomes by implementing the PBL model, four activities are applied, namely planning, implementing, observing, and reflecting. In Cycle I, the result indicates a percentage value of 81.25% and increased to 97.5% in Cycle II. In the implementation aspect, the learning outcome in Cycle 1 was 80.35 and increased to 96.42% in Cycle II. In another aspect, learning outcomes indicate an average score of 77.25 in Cycle I and increased to 87 in Cycle II. Therefore, it can be concluded that the model, Problembased Learning model (PBL), can produce an increase in the acquisition of students’ learning outcomes.